Strategi Komunikasi Pemasaran Telkom PT Telkom Surabaya Utara: Studi Deskriptif Kualitatif Strategi Komunikasi Pemasaran pada PT Witel Surabaya Utara - Agustin, Dwi; Indriastuti, Yudiana (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the marketing communication strategy at PT. Telkom North Surabaya. This research uses descriptive research with a qualitative approach. The sampling technique used in this study was a purposive sampling technique. The techniques used by researchers to collect data were in-depth interviews and documentation. Data analysis was carried out when writing the report using interactive analysis techniques. The communication process carried out by PT Telkom North Surabaya, namely in the outbound call section, there is a customer offering process offering additional service products, then the input (1-3 × 24 hour process) which will process through the system to be forwarded to the technician to carry out the installation that has been ordered to the customer via outbon call (OBC). Communication is carried out by giving greetings, conveying information and finally closing in offering additional product services. In offering additional services to OBC customers using social media such as Whatsapp, carring by phone and promotions via Instagram, and through certain pages that can only be accessed by the OBC team for additional ADD ON services. PT Telkom's OBC Telemarketing Marketing communication strategy has been effective, this is proven by the year 2022 according to Annas Kharisma (Manager Customer care PT.Telkom) PT. Telkom also obtained the first highest percentage for marketing reaching 117% ADD ON installation in Regional 5 (East Java) with the installation of more than 400 SSL (Secure Socket Layer).